EFIKASI HERBISIDA PRATUMBUH METIL METSULFURON TUNGGAL DAN KOMBINASINYA DENGAN 2,4-D, AMETRIN, ATAU DIURON TERHADAP GULMA PADA PERTANAMAN TEBU (Saccharum officinarum L.) LAHAN KERING - Nico Alfredo; Nanik Sriyani; Dad R.J. Sembodo (Universitas Lampung, 2012)
Metsulfuron-methyl is a herbicide that never been used as a preemergence herbicide for sugarcane. The objectives of this research was to know the efficacy of metsulfuron metyl and its combinations with 2,4-D, ametryn, or diuron in controlling weeds of sugarcane plantation.The experiment was arranged in Completely Randomized Block Design (CRBD) with twelve treatments and three replications. The treatments are metsulfu-ron-methyl at 4 g ha-1, 8 g ha-1, 12 g ha-1 and 16 g ha-1, combinations of 4 g ha-1 metsulfuron-methyl with 0,865 kg ha-1 2.4-D; 0,75 kg ha-1 ametryn; or 1,6 kg ha-1 diuron; 2.4-D at 1,3 kg ha-1; ametryn at 1 kg ha-1; diuron at 2 kg ha-1; manual treatment and control plot. The comparisson of mean were tested by Honestly Significant Difference (HSD) test at 5% level. Results showed that metsulfuron-methyl (at 12-16 g ha-1) could supress total weeds biomass until 8 weeks after application (WAA). Combinations between metsulfuron-methyl with 2,4-D, ametryn or diuron showed better efficacy than single metsulfuron-methyl application. All herbicides did not cause phytotoxicity symtoms to sugarcane. Key words: 2,4-D, ametryn, diuron, combination, efficacy, metsulfuron-methyl, weed, sugarcane.